E-Government Development Index Impact on World Governance Indicator Index in Southeast Asian Countries - Mohamad Sukarno; Achmad Nurmandi (Journal of Contemporary Governance and Public Policy, 2023)
The aims of this study is to find out how the E-Government Development Index (EGDI) affects the World Governance Index (WGI) in Southeast Asia. The choice of a Southeast Asian country is important because, in general, Southeast Asia is a developing country that needs improvement, especially in the area of government. Southeast Asian countries still have governance that hasn't worked well as a whole, and non-government actors still have the most power. The method used in the research is quantitative machine learning (Google Collab Research) analysis. Data processing is carried out in the form of extras from EGDI and WGI in Southeast Asian countries to find the influence of the two data sets. The results showed that the impact of EGDI on WGI was the greatest in the indicators of government effectiveness and regulatory quality, with a score above 0.53. The reason behind this is the increase in digital bureaucracy in all sectors of government; it also has an impact on good governance. Then, in the sector of corruption control, some countries have also adopted ICT, and some of them have succeeded in reducing corruption. Sectors that have adopted digital bureaucracies, such as education, environment, crisis management, and sustainable development. In the regulatory quality sector, institutional improvements are carried out to suppress corruption and improve the quality of democracy by involving non-governmental actors. The lowest indicator is voice and accountability, with a score below 0.49 (moderate). This is because there is still a lot of development in terms of governance and government institutions, which have not run optimally.